2007
DOI: 10.1007/s11274-007-9438-z
|View full text |Cite
|
Sign up to set email alerts
|

Cometabolic degradation of polychlorinated biphenyls (PCBs) by axenic cultures of Ralstonia sp. strain SA-5 and Pseudomonas sp. strain SA-6 obtained from Nigerian contaminated soils

Abstract: Substantial metabolism of 2,3,4,5-tetrachlorobiphenyl (2,3,4,5-tetraCB) and 2,3¢,4¢,5-tetraCB by axenic cultures of Ralstonia sp. SA-5 and Pseudomonas sp. SA-6 was observed in the presence of biphenyl supplementation, although, the strains were unable to utilize tetrachlorobiphenyls as growth substrate. The former was more amenable to aerobic degradation (~70% degradation) than the latter (22-45% degradation). Recovery of 2,5-chlorobenzoic acid and chloride from 2,3¢,4¢,5-tetraCB assay is an indication of init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Arrows indicate the direction and magnitude of environmental parameters associated with major genera. Each circle represents a subsample of CWW active sludge (A: 1, 2, 3; O 1 : 4, 5, 6; O 2 : 7, 8, 9) (Adebusoye et al 2008) and dimethylsulfide (Arellano-Garcia et al 2009). At the same time, Thiobacillus was found to be responsible for the denitrification (Vishnivetskaya et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arrows indicate the direction and magnitude of environmental parameters associated with major genera. Each circle represents a subsample of CWW active sludge (A: 1, 2, 3; O 1 : 4, 5, 6; O 2 : 7, 8, 9) (Adebusoye et al 2008) and dimethylsulfide (Arellano-Garcia et al 2009). At the same time, Thiobacillus was found to be responsible for the denitrification (Vishnivetskaya et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The major genera detected in anaerobic active sludge was dominated by Pseudomonas (72.59 %), followed by Alkaliphilus (6.27 %), Comamonas (5.67 %), Campylobacter (1.91 %), and Pusillimonas (1.44 %). It was reported that the genus of Pseudomonas had the ability to degrade quinolone, pyridine, and pyrene (Bai et al 2011a;Deng et al 2012;Zhang et al 2014) and related to the biodegradation of refractory organics (Adebusoye et al 2008) Table S2 and Fig. 4 show the comparison of the major genera.…”
Section: Phylogenetic Diversity Analysis Of Sequencesmentioning
confidence: 99%
“…It was observed that the consortia derived from anaerobic sludge and amended with electron donors quantitatively and incompletely degraded PCE to cis-dichloroethylene, whereas in reactors augmented with a dehalogenating culture complete dechlorination of PCE occurred even in the presence of additional toxic contaminants. Adebusoye et al (2008) have observed substantial metabolism of 2,3,4,5-tetrachlorobiphenyl (2,3,4,5-tetraCB) and 2,3 0 ,4 0 ,5-tetraCB by axenic cultures of Ralstonia sp. SA-5 and Pseudomonas sp.…”
Section: Co-metabolismmentioning
confidence: 99%
“…There is much interest in environmental contamination from persistent organic pollutants (POPs) due to their pervasiveness in the environment. Studies on the prevalence , and remediation of molecules such as polybrominated biphenyls (PBBs) and polychlorinated biphenyls (PCBs) provide evidence concerning the scope of the POP problem. Several studies on PBBs and PCBs , document their environmental persistence and propagation in fish and river sediments.…”
Section: Introductionmentioning
confidence: 99%